Rolle und Grenzen der Vertebro-/Kyphoplastie im Metastasenmanagement der Wirbelsäule = Role and limitations of vertebroplasty and kyphoplasty in the management of spinal metastases - Akbar, Michael; Eichler, Markus; Hagmann, Sébastien; Lehner, Burkhard; Hemmer, Stefan; Kasperk, Christian; Wiedenhöfer, Bernd (Der Orthopäde, 2012)
The spine is the most common site for skeletal metastases. Tumor-induced osteolysis may lead to pain, dysfunction and ultimately vertebral fracture. In some patients conventional surgery is not suitable because of the palliative therapy approach. Just for this patient population it was shown that cement augmentation of the vertebra is an effective therapy option and plays an important role. Nevertheless, cement augmentation of the vertebra has its limitations and should only be applied by appropriate indications.
Gesehen am 06.04.2018